PENGARUH DIGITALISASI PEMBELAJARAN, KOMPETENSI PROFESIONAL DAN KOMITMEN KERJA DIMODERASI OLEH BUDAYA ORGANISASI TERHADAP PRESTASI SISWA (STUDI EMPIRIS PADA SMP NEGERI DI KOTA MAKASSAR) - Muhammad Fajri; Herman Jelatu (Pojok Publisher, 2024)
Teachers have an important role in the formation of character and attitudes of students. It is said that teachers are qualified because of their role in developing the intellectual, emotional, and spiritual of students. The purpose of this study was to determine the effect of digitalization of learning, professional competence and work commitment moderated by organizational culture on student achievement at Public Junior High Schools in Makassar City. The approach in this study used quantitative research. The sample selected teachers at several Public Junior High Schools in Makassar City were determined as many as 100 teachers. The results of the study obtained the findings that digitalization of learning had a positive and significant effect on student achievement. Professional competence had a positive and significant effect on student achievement. Work commitment had a positive and significant effect on student achievement. The results of the moderation test obtained the findings that organizational culture could not moderate the effect of digitalization of learning on student achievement. Organizational culture moderates or strengthens and significantly the effect of professional competence on student achievement. Then organizational culture moderates or strengthens and significantly the effect of work commitment on student achievement at several Public Junior High Schools in Makassar.